PENGARUH FERMENTASI LIMBAH RUMEN SAPI DAN RAGI TERHADAP PERFORMA KOMPOR BIOGAS - Husnawati Yahya (Lingkar : Journal of Environmental Engineering, 2022)
This study aims to examine the effect of fermenting cow rumen waste and yeast on biogas stove performance. This study uses a quantitative approach with experimental methods starting with the stages of designing, assembling, testing the design results, observing and processing data. In this study, to get good biogas results, it was carried out in a 2:1 ratio pf water mixed with yeast and cow’s rumen. The fermantation process takes 8 to 31 days, during which the cow’s rumen needs to be stirred regularly to prevent solid particles from setting at the bottom of the digester.